Основні етапи розвитку науково-довідкового апарату державних архівів в Україні за радянської доби - Христова, Н. (Архіви України, 2008)
The article displays the tendencies and mechanisms of reference apparatus development in terms of the state archives documents; highlights the issue of descriptive methods and techniques development, describes legal and methodical regulation of the state archival service with regard to the type structure of archival retrieval means in 1920–1990.